EFEKTIFITAS PENGGUNAAN DRY NEDDLING UNTUK MENURUNKAN NYERI PADA OSTEOARTHRITIS - Fahruddin, Sri Gunda Fahriana; Nugraha, Rahmat; Diya Atiqa, Ulfa (Universitas Muhammadiyah Metro, 2025)
Introduction: Osteoarthritis is a chronic and progressive joint disorder usually characterised by damage to the cartilage located at the joints of the bones. This cartilage damage can be caused by mechanical stress or biochemical changes in the body. The occurrence of Osteoarthritis is influenced by various risk factors such as age (aging process), genetic, obesity, joint injury, disease Many high quality research studies are needed in these findings, so it is necessary to assess the effect of dry needling on reducing pain in patients with Osteoarthritis. Dry Needling (DN) is a technique used in the management of various neuromusculoskeletal pain syndromes by inserting fine monofilament needles through the skin. DN uses needles similar to those used in acupuncture, but the application technique is different. In DN, the needle is moved up and down within the muscle, precisely in the area of the myofascial trigger point (MTrP). This study aims to determine the benefits of dry needling in reducing pain in Osteorthritis. Methods: This research uses the literature study/literature review method. Where data searches are obtained through literature search engines using a combination of keywords according to the topic. After reviewing selected journals or articles, literature data analysis is carried out by classifying, directing, eliminating unnecessary data and organising data in such a way that it ends in a conclusion. Results: the use of Dry Neddling (DN) can reduce pain in patients with Osteoarthritis. Keywords: Osteoarthritis; Dry Neddling; Pain